In-situ reduction by Joule heating and measurement of electrical conductivity of graphene oxide in a transmission electron microscope. (6th April 2021) - Hettler, Simon; Sebastian, David; Pelaez-Fernandez, Mario; Benito, Ana M; Maser, Wolfgang K; Arenal, Raul
Abstract: Graphene oxide (GO) is reduced by Joule heating using in-situ transmission electron microscopy (TEM). The approach allows the simultaneous study of GO conductivity by electrical measurements and of its composition and structural properties throughout the reduction process by TEM, electron diffraction and electron energy-loss spectroscopy. The small changes of GO properties observed at low applied electric currents are attributed to the promotion of diffusion processes. The actual reduction process starts from an applied power density of about 2 × 10 14 Wm −3 and occurs in a highly uniform and localized manner. The conductivity increases more than 4 orders of magnitude reaching a value of 3 × 10 3 Sm −1 with a final O content of less than 1%. We discuss differences between the reduction by thermal annealing and Joule heating.